2017
DOI: 10.5530/pj.2017.5.97
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antioxidant Activity of Black Mulberry (Morus nigra L.) Extract for Acne Treatment

Abstract: Introduction:Black mulberry is rich in phenols and is hence usable in the treatment of acne. It also contains anthocyanin, a well-known antioxidant. This study aimed to examine the antibacterial and antioxidant properties of black mulberry (Morus nigra L.) extract as a potential raw material for use in beauty care products. Method: Fruit extract was obtained using maceration method with 96% ethanol. The antibacterial activity of the extract was determined by disc diffusion method, while the minimal inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
(14 reference statements)
0
18
0
1
Order By: Relevance
“…2,3 Some of the bacteria that cause acne include P. acnes, S. epidermidis, and S. aureus. 4,5 In Indonesia, around 95-100% of young men and 83-85% of young women suffering from acne. The prevalence of acne in adult women is around 12% and 3% in adult men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Some of the bacteria that cause acne include P. acnes, S. epidermidis, and S. aureus. 4,5 In Indonesia, around 95-100% of young men and 83-85% of young women suffering from acne. The prevalence of acne in adult women is around 12% and 3% in adult men.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was found that acne is a skin problem until past adolescence with a higher prevalence of women than men in the age range of 20 years or more. 5,6 Giving antibiotics is one alternative acne treatment that aims to reduce the bacterial population. However, giving antibiotics to acne patients was reported to increase the occurrence of upper respiratory tract infections when compared with acne patients without antibiotic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…10 DPPH assay is most suitable for polar compounds because the DPPH crystals can dissolve easily in a commonly solvent and give maximum absorbance. 28 Based on Figure 2, E2 and E3 shows greater % scavenging effect, compared to E1. TPC of T. hempricii related with the antioxidant activity.…”
Section: Discussionmentioning
confidence: 89%
“…The phenol content of black mulberry fruit can provide pharmacological activities such as antioxidant 13 , antibacterial 14 , hypolipidemic effect 15 and macrophage activation effect 16 . The highest concentration of phenol can be found in black mulberry fruit (Morus nigra L) 17 , and with this high phenolic content black mulberry has potential for antioxidant activity 1,18 .…”
Section: Chemical Constituents and Pharmacological Activitymentioning
confidence: 99%